Food Insecurity in Tribal High Migration Communities in Rajasthan, India. Issue 4 (December 2020) - Saxena, Anupriya; Amin, Arpita; Mohan, Sanjana Brahmawar; Mohan, Pavitra
Background: The COVID pandemic and subsequent lockdown has disrupted food supplies across large parts of India, where even prior to the pandemic, food insecurity and malnutrition were widely prevalent. Tribal populations in southern Rajasthan, India, live in extreme scarcity, rely mainly on outward migration for sustenance, and have been significantly affected by the pandemic. In this study, we assess the availability of foodstuffs at the household level and community experiences about satiety and hunger during lockdown. Methodology: We conducted a rapid assessment of food security in rural southern Rajasthan, India, using a structured questionnaire. Trained interviewers conducted telephonic interviews using KoBoToolbox, an open-source tool. A total of 211 respondents including community volunteers, family members of tuberculosis patients and malnourished children, pregnant women, and influential members in the villages participated in the study. Results: A cereal was reported to be present by 97% of the respondents, two-thirds had pulses, and nearly half had milk. The amount of cereals available was adequate for about 5 months and that of pulses, oil/ ghee, and sugar for about 1 to 2 weeks. Two-thirds of the respondents reported that food in their households was sometimes not sufficient for the amount they wanted to eat, and 97% of these mentioned not having money to buy food as the reason for not having sufficient food. Conclusion: This study highlights widespread food insecurity among tribal communities in southern Rajasthan, and the scenario is likely to be similar in other tribal migration dependent areas of the country.